2017
DOI: 10.1039/c7ra10517g
|View full text |Cite
|
Sign up to set email alerts
|

Novel type ketone-substituted metallophthalocyanines: synthesis, spectral, structural, computational and anticancer studies

Abstract: This work reports on the synthesis and characterization of phthalocyanines (M = Cu(ii) (2), Zn(ii) (3) In(iii) (4) and Co(ii) (5)) peripherally tetra-substituted with 1-(4-hydroxyphenyl)propan-1-one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…A previous study by our group, it was found that phthalocyanines containing 1‐(4‐hydroxyphenyl)propan‐1‐one groups in non‐peripheral positions have promising results for cancer applications, have good solubility, and reduce aggregation tendency. In addition, it has been determined that phthalocyanines with this functional group are sensitive to acidic conditions 19 . Surprisingly, within the scope of this study, ketone groups were converted to imine groups under suitable conditions, and it was observed that these newly synthesized phthalocyanines showed high sensitivity to acidic conditions when compared to their precursor phthalocyanine derivatives.…”
Section: Introductionmentioning
confidence: 84%
“…A previous study by our group, it was found that phthalocyanines containing 1‐(4‐hydroxyphenyl)propan‐1‐one groups in non‐peripheral positions have promising results for cancer applications, have good solubility, and reduce aggregation tendency. In addition, it has been determined that phthalocyanines with this functional group are sensitive to acidic conditions 19 . Surprisingly, within the scope of this study, ketone groups were converted to imine groups under suitable conditions, and it was observed that these newly synthesized phthalocyanines showed high sensitivity to acidic conditions when compared to their precursor phthalocyanine derivatives.…”
Section: Introductionmentioning
confidence: 84%
“…The HOMO and LUMO values of the molecules were used to explain the molecular activity. The chemical reactivity parameters of the molecules, such as Energy of the Highest Occupied Molecular Orbital ( E HOMO ), Energy of the Lowest Unoccupied Molecular Orbital (E LUMO ), Δ E (HOMO – LUMO energy gap), electronegativity ( χ ), chemical potential ( μ ), chemical hardness ( η ), electrophilicity ( ω ), nucleophilicity ( ε ), global softness ( σ ), and proton affinity (PA) were used to obtain information about the activities of the molecules: μ=χ=ENυ()r η=122EN2υ()r=12()μN …”
Section: Methodsmentioning
confidence: 99%
“…[22] It is well known that the substitution of bulky groups in the peripheral/nonperipheral positions of phthalocyanines increases their solubility in common organic solvents. Phthalocyanines containing 1-(4-hydroxyphenyl) propane-1-one groups previously synthesized by our group have been found to have very high solubility in many organic solvents such as CHCl 3 , CH 2 Cl 2 , THF, toluene, DMF, and DMSO, [23,24] and within the scope of this study, it was found that the electronic spectra of novel octa-substituted phthalocyanine derivatives bearing 1-(4-hydroxyphenyl)propane-1-one are highly dependent on acid concentration. The green color of phthalocyanines was changed to pale green in the presence of HCl, which can be observed even with the naked eye.…”
Section: Introductionmentioning
confidence: 99%